A framework for overcoming disparities in management of acute coronary syndromes in the Australian Aboriginal and Torres Strait Islander population. A consensus statement from the National Heart Foundation of Australia. Issue 11 (16th June 2014) - Ilton, Marcus K; Walsh, Warren F; Brown, Alex D H; Tideman, Philip A; Zeitz, Christopher J; Wilson, Jinty
Summary: Aboriginal and Torres Strait Islander patients with acute coronary syndromes (ACS) experience lower intervention rates and poorer outcomes compared with non‐Indigenous patients. A broad range of geographical, cultural and systemic factors contribute to delays and suboptimal treatment for ACS. Every Indigenous ACS patient, regardless of where they live, should be able to expect a coordinated, patient‐centred pathway of care provided by designated provider clinical networks and supported by Indigenous cardiac coordinators, Aboriginal liaison officers (ALOs) and health workers. These designated provider clinical networks provide: ➢ appropriate prehospital and inhospital treatment ➢ an individualised patient care plan developed jointly with the patient and his or her family ➢ culturally appropriate education initiated within the hospital setting and involving families with support from ALOs ➢ effective follow‐up care and access to relevant secondary prevention programs. We outline generic pathways to provide policymakers, health planners and health care providers with a framework for ACS diagnosis and management that can be implemented across the diverse settings in which Aboriginal and Torres Strait Islander people reside and their care is delivered, in order to optimise care and assertively address the current disparities in outcomes.